Geometric thinking program to enhance problem-solving skills of primary school teacher candidates - T. Trimurtini; Nursiwi Nugraheni; Budi Waluya; Elok Fariha Sari (Universitas Muhammadiyah Malang, 2024)
Geometry is a mathematics subject that has been widely considered hard. Several problems in learning geometry lead to geometric problem-solving skills. After exploring various causes, theories, and processes of geometric thinking, there should be an evaluation program to optimize problem-solving skills. This study aims to (1) develop a geometric thinking evaluation program and (2) enhance geometric problem-solving skills observed from the students’ thinking level. The research and development adopted the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model, which started from the analysis stage involving four lecturers and 306 of students. The research was conducted at Primary School Teacher Education Department, Universitas Negeri Semarang. The process continued to the design stage, at which the evaluation program was drafted, followed by the development stage to test the validity. The last two phases included the trials in which the t-test and n-gain were applied to measure the program's effectivity and the evaluation phase aimed at assessing its practicality and the student's achievement in geometry. The established evaluation program covers an instrument of 39 multiple-choice items as an early assessment to determine the thinking level and learning trajectories as a scaffolding for improving geometric thinking skills. The trajectories, in the form of worksheets, were adjusted to the students' thinking level and were effective in assisting them in elevating to the informal reasoning level as well as refining their problem-solving skills.